2012
DOI: 10.1182/blood-2012-04-426643
|View full text |Cite
|
Sign up to set email alerts
|

NKT cell adjuvant-based tumor vaccine for treatment of myc oncogene-driven mouse B-cell lymphoma

Abstract: Immunomodulators are effective in controlling hematologic malignancy by initiating or reactivating host antitumor immunity to otherwise poorly immunogenic and immune suppressive cancers. We aimed to boost antitumor immunity in B-cell lymphoma by developing a tumor cell vaccine incorporating ␣-galactosylceramide IntroductionHematologic malignancies typically express the necessary machinery for eliciting antitumor immunity, such as costimulatory molecules, yet many tumors are poorly immunogenic. Therapeutic vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
121
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(131 citation statements)
references
References 48 publications
3
121
2
1
Order By: Relevance
“…To maximally harness such immunological cascades, we established an efficient system using cells bearing a cell-associated Ag along with the iNKT cell ligand, a-galactosylceramide (a-GalCer). For example, we used iNKT ligand-loaded, tumor-associated Ag (TAA)-expressing CD1d + tumor cells (tumor/Gal) (19)(20)(21) or allogeneic fibroblasts loaded with a-GalCer transfected with TAA mRNA (16,22).…”
mentioning
confidence: 99%
“…To maximally harness such immunological cascades, we established an efficient system using cells bearing a cell-associated Ag along with the iNKT cell ligand, a-galactosylceramide (a-GalCer). For example, we used iNKT ligand-loaded, tumor-associated Ag (TAA)-expressing CD1d + tumor cells (tumor/Gal) (19)(20)(21) or allogeneic fibroblasts loaded with a-GalCer transfected with TAA mRNA (16,22).…”
mentioning
confidence: 99%
“…We identified several mechanisms by which C1498 cells could suppress immune responses, including increased proportions of Tregs and Other groups have also shown that a-GalCer-pulsed acute leukemia cells can be used as a prophylactic vaccine. By using the AML cell line AML-ETO9a, Mattarollo et al 23 showed that irradiated a-GalCer-pulsed AML cells prevented the development of AML in the prophylactic setting but only delayed progression when administered therapeutically, and Shimizu et al 29 demonstrated effective prophylactic vaccination by using the myelomonocytic WEHI-3B model. Our experiments extend these findings by elucidating immunosuppressive activities in established leukemia and indicating that protection against acute leukemia can also be invoked during remission after cytarabine chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…23,47,63 Although CD1d is weakly expressed on C1498 cells and has been identified in other acute leukemic cell lines, including AML-ETO9a, 23 EL4, and WEHI-3B (L.R.A, unpublished data, June 14, 2014), we have previously demonstrated that a CD1d-negative a-GalCer-pulsed glioma vaccine can provide protection against glioma challenge. 25 We have also shown that CD1d-deficient DCs can transfer a-GalCer to host resident CD1d-expressing antigenpresenting cells in vivo to induce potent invariant NKT-cell activation, which likely reflects transfer of a-GalCer embedded within membranes of the injected cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations